2000
DOI: 10.1074/jbc.275.1.605
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That 2-Arachidonoylglycerol but Not N-Palmitoylethanolamine or Anandamide Is the Physiological Ligand for the Cannabinoid CB2 Receptor

Abstract: We examined the effect of 2-arachidonoylglycerol, an endogenous cannabinoid receptor ligand, on the intracellular free Ca 2؉ concentrations in HL-60 cells that express the cannabinoid CB2 receptor. We found that 2-arachidonoylglycerol induces a rapid transient increase in intracellular free Ca 2؉ concentrations in HL-60 cells. The response was affected by neither cyclooxygenase inhibitors nor lipoxygenase inhibitors, suggesting that arachidonic acid metabolites are not involved. Consistent with this notion, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
271
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(285 citation statements)
references
References 48 publications
11
271
1
2
Order By: Relevance
“…In 1992, when Devane et al identified AEA as a ligand for CB1 receptors, it seemed reasonable to expect that this lipid was only the first representative of a larger family of endocannabinoids (Devane et al, 1992). Indeed, ensuing studies identified a second endocannabinoid, 2-AG, that acts as a full agonist on CB1 and CB2 receptors (Mechoulam et al, 1995;Sugiura et al, 1995Sugiura et al, , 2000Stella et al, 1997). In this study, we show that neurons and microglial cells produce four endocannabinoids: the two well known endocannabinoids, AEA and 2-AG, as well as the two new endocannabinoids, HEA and DEA.…”
Section: Discussionmentioning
confidence: 99%
“…In 1992, when Devane et al identified AEA as a ligand for CB1 receptors, it seemed reasonable to expect that this lipid was only the first representative of a larger family of endocannabinoids (Devane et al, 1992). Indeed, ensuing studies identified a second endocannabinoid, 2-AG, that acts as a full agonist on CB1 and CB2 receptors (Mechoulam et al, 1995;Sugiura et al, 1995Sugiura et al, , 2000Stella et al, 1997). In this study, we show that neurons and microglial cells produce four endocannabinoids: the two well known endocannabinoids, AEA and 2-AG, as well as the two new endocannabinoids, HEA and DEA.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,22,56 In the present study we compared the effects of 2-AG with that of the other endocanabinoids (AEA, PEA, POEA), the natural cannabinoids (␦ 8 -THC, ␦ 9 -THC, cannabinol, cannabidiol), and the synthetic molecules (WIN55212-2, CP55940).Among the endocannabinoids, 2-AG was the most potent inducer of migration, supporting the idea that 2-AG is the true endogenous ligand for the peripheral cannabinoid receptor. [56][57][58][59] AEA, which was the first endogenous cannabinoid ligand isolated, 22 shows similar binding affinity to the Cb2 receptor as 2-AG does. 59 However, AEA only weakly stimulated migration of Cb2-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Anandamide was first isolated from brain and initially characterized as an endogenous ligand for cannabinoid receptors. Although agonist activity at both CB1 and CB2 receptors has been demonstrated, 8,9 anandamide also acts as an agonist at a vanilloid (VR1) or capsaicin receptor. [10][11][12][13] In addition, direct modulation of NMDA receptor activity by AEA has also been described.…”
Section: Introductionmentioning
confidence: 99%